The Audiovisual Media: Allies or Enemies of the State in Costa Rican Cultural Dissemination? (1950-2000)3 - Ruiz Siles, Yanina (2024)
The objective of this research is to explore the role that audiovisual media has played in the dissemination of Costa Rican culture and national identity by state institutions. Culture is susceptible to transformations due to external factors and audiovisual media is usually associated with the dissemination of mass culture and/or the loss of national culture. The three most used audiovisual media during the second half of the 20th century, that is, cinema, radio, television, were analyzed to demonstrate the use that the State has made of them throughout the study period. Through national legislation, as well as the institutional memories of the MEP and the MCJD from the years 1950 to 2020, the behavior of public entities in the media was analyzed. The study shows that audiovisual culture has evolved significantly in the last century and that its impact on culture is unquestionable. The function of audiovisual media adapts to the contexts, which is why State policies regarding cultural dissemination have been innovated and renewed over the years.